Upaya Guru dalam Pengembangan Bakat Olahraga Catur pada Anak Tunanetra di SLB Cendana Rumbai - Laras Ayuningtiyas; Zulmiyetri Zulmiyetri (Jurnal Penelitian Pendidikan Khusus, 2021)
The study aims to describe the teacher's efforts in developing the talent for the sport become an achievement for the blind child focused on the teacher's efforts, the obstacle faced, the way the teacher tackles the challenges faced in the development of a chess talent. To better describe the teacher's efforts, researchers use a qualitative descriptive approach. Data collection techniques using observation, interviews, and documentary studies. The results of the study revealed that teachers' efforts in developing chess talent by viewing opportunities and potential as a way of identifying children. Teachers, in turn, practice extracurricular activities by the talent development team and supplement the infrastructure system of blind chess boards. Teachers provide motivation, attention, reward, cooperation with a professional trainer, build good communication with parents and assist with child training and compete so that the blind child maximize the talents in chess that are in a national level.